Application of SARS-CoV-2 Serology to Address Public Health Priorities - Sherman, Amy C.; Smith, Teresa; Zhu, Yerun; Taibl, Kaitlin; Howard-Anderson, Jessica; Landay, Taylor; Pisanic, Nora; Kleinhenz, Jennifer; Simon, Trevor W.; Espinoza, Daniel; Edupuganti, Neena; Hammond, Skyler; et al. (Frontiers in Public Health, 2021)
Background: Antibodies against SARS-CoV-2 can be detected by various testing platforms, but a detailed understanding of assay performance is critical. Methods: We developed and validated a simple enzyme-linked immunosorbent assay (ELISA) to detect IgG binding to the receptor-binding domain (RBD) of SARS-CoV-2, which was then applied for surveillance. ELISA results were compared to a set of complimentary serologic assays using a large panel of clinical research samples. Results: The RBD ELISA exhibited robust performance in ROC curve analysis (AUC> 0.99; Se=89%, Sp=99.3%). Antibodies were detected in 23/353 (6.5%) healthcare workers, 6/9 RT-PCR-confirmed mild COVID-19 cases, and 0/30 non-COVID-19 cases from an ambulatory site. RBD ELISA showed a positive correlation with neutralizing activity (p = <0.0001, R2 = 0.26). Conclusions: We applied a validated SARS-CoV-2-specific IgG ELISA in multiple contexts and performed orthogonal testing on samples. This study demonstrates the utility of a simple serologic assay for detecting prior SARS-CoV-2 infection, particularly as a tool for efficiently testing large numbers of samples as in population surveillance. Our work also highlights that precise understanding of SARS-CoV-2 infection and immunity at the individual level, particularly with wide availability of vaccination, may be improved by orthogonal testing and/or more complex assays such as multiplex bead assays.